Patterns of Retentive Failures in Dislodged Single Crowns: Retentive failures in crowns - Sharif, Mubashir; Aslam, Samina; Khan, Imran; Rehman, Abdul; Khan, Mansoor; Afzal, Muhammad (Pakistan Armed Forces Medical Journal, 2022)
Objective: The study aimed to ascertain the prevalence of retentive failure patterns of single crowns leading to de-cementation of the crowns and to estimate their average length of service. Study Design: Cross-sectional study. Place and Duration of Study: Department of Prosthodontics, Armed Forces Institute of Dentistry, Rawalpindi Pakistan, from May to Nov 2020. Methodology: 80 patients were selected using the non-probability Consecutive sampling technique. Both male and female patients with only single-unit crowns were included. In addition, the material used for the fabrication of crowns, years of service and site of retentive failure were recorded. Results: Female patients (41, 51.3%) reported more frequently than males (39, 48.8%). The majority of the dislodged crowns (41, 51.3%) concerned the mandibular posterior region. Almost half of the crowns (44, 55%) dislodged due to fracture occurring at the interface of restoration and the cement. 68.8% of crowns served for 1-3 years before dislodgement. Most of the dislodged restorations (30, 37.5%) were provided by general dentists. Conclusion: Mandibular posterior crowns were the most prevalent crowns that were dislodged, and the estimated length of most of the crowns was up to 3 years. Therefore, the anatomy of the tooth being prepared must be considered before preparing the tooth so that retentive failure may be reduced, thus improving the overall length of service.